The Internet and the Ability to Innovate in Latin America - Alberto Chong; Alejandro Micco (Inter-American Development Bank, Research Department, 2002)
In this paper we provide an overview of the situation of the Internet in Latin America and argue that, although latecomers, Latin American countries could in principle catch up at a faster pace and a lower cost. But that will depend on the environment for innovation in the countries; in that respect, the adoption of the Internet may prove to be no different than other technological changes. The paper also discusses how the degree of innovativeness in a country helps explain the extent to which new technologies may be more effectively absorbed. What is surprising about this relationship is that it is valid even when isolating the fact that countries with better telephone infrastructure are also the ones with more Internet hosts. We found that the capacity to innovate and assimilate new technologies is not just a matter of income or infrastructure endowment.
Keywords: 330; Internet; Innovationsdiffusion; Lateinamerika